Educational Technologies in Modern Higher Education Institutions (Analysis of Russian and Foreign Research and Practice) - N. V. Bordovskaia; E. A. Koshkina; N. A. Bochkina (Russian State Vocational Pedagogical University, 2020)
Introduction. Globalisation, openness to innovation, implementation of digital content, realisation of competency-based approach in modern education generate a consistent tendency towards strengthening of the role of educational technologies (ET) in different types of professional pedagogical activity, reinforcing pertinence of their application at all levels of education. Mastery and efficient use of a wide range of educational technologies have expanded the opportunities for educators to use productively traditional pedagogical and digital information technologies in order to obtain the guaranteed intended (expected) educational outcome. The interest of researchers and practitioners in selection, design, implementation and evaluation of effectiveness of educational technologies in higher educational institutions is evidenced by the increase in the number of publications suggesting various points of view on the use of such technologies within the educational process, in educational communications and in professional and personal development of students. The search for the most effective means of training of the new generation of specialists to achieve academic and technological breakthrough in Russia has increased the significance of systematic scientific information on modern educational technologies used in higher education institutions.The aim of the current research is to present the results of review and systematisation of research information on theoretical foundations of development and application of educational technologies in Russian and foreign higher educational institutions.Methodology and research methods. Analytical review has been prepared based on systematisation and generalisation of foreign and Russian scientific publications dedicated to the issues of design and use of educational technologies in the higher educational practice. 319 sources published since 2010 and included in Web of Science and Scopus research and citation databases as well as in the Russian Science Citation Index have been analysed. In order to achieve the set objective, authors have used such methods as content analysis, systems analysis, comparative analysis and benchmarking, terminological analysis, context analysis, generalisation and systematisation, analytical grouping, as well as methods of mathematical statistics.Results and scientific novelty. The article contains the results of analysis of Russian and foreign publications based on the following: 1) levels of presentation of research information (theoretical, theoretical and experimental, empirical); 2) attributes and properties of educational technologies; 3) approaches to selection of classification principles of educational technologies; 4) capabilities of educational technologies to shape academic, communicative and professional competency of a specialist; 5) criteria for evaluation of effectiveness of application of ET in the higher educational practice; 6) preparedness of teacher of higher educational institutions to develop and apply educational technologies. It has been established that Russian authors are still more oriented towards describing the characteristics and algorithms of predominantly traditional educational technologies and their applicability, evaluating their effectiveness through influencing students' professional and personal development and competent communication. Foreign authors prefer to assess how widely applicable digital educational technologies are (within the boundaries of the educational organisation and beyond), measure students' acceptance of educational technologies and their effectiveness through the impact on improvement of educational quality. Statistically significant differences were identified for all considered functional characteristics of educational technology in Russian and foreign publications, with the exception of "Student Attitude to Educational Technology". Both Russian and foreign authors in the last 5 years have increased their interest in mixed educational technologies and in the problems of integrating traditional and digital technologies in higher education. In Russian journals there is an increase of the number of publications about the digital technologies, and in foreign publications there is an increase in the number of publications on traditional technologies, resources and conditions for improvement of effectiveness of educational technologies.Practical significance. The materials of the article can be used in the higher educational practice and in further research on development and application of educational technologies in Russian and foreign higher education.